A new approach for evaluating the ductility, volumetric stiffness and permeability of cut-off wall backfill materials. Issue 2 (20th April 2018) - Ostrowsky, J. L.
Abstract : The behaviour of soil–cement and plastic concrete cut-off walls in dams is critically affected by ductility and volumetric stiffness. Post-construction deformation of cut-off walls is common due to the differences in strength and stiffness of the wall and the surrounding embankment material and changes in loading due to changes in the seepage regime. Conventional concrete barriers crack as they deform creating regions of high permeability and concentrated flow in the cracked region. Ductile barriers such as soil–bentonite walls will deform without cracking, but lack structural integrity. The behaviour of intermediate materials, such as soil–cement and plastic concrete, is currently not well understood. A laboratory testing procedure has been developed to quantify the ductility of soil–cement and plastic concrete relative to changes in permeability (hydraulic conductivity) with strain. Tests were performed on a number of soil–cement specimens having varying cement and bentonite contents. The test results show that this method is effective in illustrating and quantifying the differences in behaviour of the soil–cement specimens and effectively measuring low-permeability materials (10 −6 –10 −8 cm s −1 ). This procedure can be instrumental for defining and quantifying the properties of soil–cement mixtures and plastic concrete used for cut-off wall backfill materials.